2004
DOI: 10.21608/ejabf.2004.1807
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Some Histological and Biochemical Aspects in Fishes From Qarun and Bardawil Lakes

Abstract: M^l e specimens of Tilapia zillii. Magil cephalus. Liza ramada and Soiea egyptiaca were collected from Ayoub and Shakshouk Stations at the west and middle of Qarun Lake. At the same period, other male specimens of M. cephalus. L. ramada and Solea vulgaris were collected from Bardawil Lake. The histological and biochemical findings can be summarized as follows: Histological examination of gills, liver and kidney of the four studied fish species in both lakes showed variable pathological changes. Bardawil Lake f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In the present study, the highest average value of surface water temperature was recorded at Village 8 during summer and the lowest occurred at Nema Island during winter. The present findings were nearly similar to that obtained by Elgaid (1980); Abdel-Monem (1991); Ahmed (1994); Khalaf-Allah (2001); Gaber et al (2004); Abdel-Satar et al 2010; Rabeh (2012) and Afifi (2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the highest average value of surface water temperature was recorded at Village 8 during summer and the lowest occurred at Nema Island during winter. The present findings were nearly similar to that obtained by Elgaid (1980); Abdel-Monem (1991); Ahmed (1994); Khalaf-Allah (2001); Gaber et al (2004); Abdel-Satar et al 2010; Rabeh (2012) and Afifi (2015).…”
Section: Discussionsupporting
confidence: 92%
“…The present study indicated that, the highest values of hydrogen ion concentrations were recorded at Village 8 Station during summer (8.67±0.15) and autumn (8.76±0.02) and the lowest values were detected at Ezbet Abd El-Alim Station during spring (7.96±0.09) and winter (7.96±0.12). This observation was matching with Gaber et al (2004); Abou El-Gheit et al (2012) and Afifi (2015) and not matching with that obtained by Rabeh (2003); Rabeh & Fareed (2006) and Rabeh (2012) whom recorded that, the low values of hydrogen ion concentrations during summer; this may be due to the degradation of organic matter in the sediment.…”
Section: Discussionmentioning
confidence: 51%